2015
DOI: 10.1080/2162402x.2015.1014246
|View full text |Cite
|
Sign up to set email alerts
|

BTLA marks a less-differentiated tumor-infiltrating lymphocyte subset in melanoma with enhanced survival properties

Abstract: (2015) BTLA marks a less-differentiated tumor-infiltrating lymphocyte subset in melanoma with enhanced survival properties, OncoImmunology, 4:8, e1014246,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 48 publications
1
47
0
Order By: Relevance
“…Our previous report demonstrated that CD8 + BTLA + human TIL produce more IL-2 upon activation (14). Thus, we further investigated whether BTLA signaling could be responsible for IL-2 secretion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous report demonstrated that CD8 + BTLA + human TIL produce more IL-2 upon activation (14). Thus, we further investigated whether BTLA signaling could be responsible for IL-2 secretion.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that the CD8 + BTLA + TIL subset had an improved proliferative capacity in response to IL-2 (14). Thus, we sought to determine whether BTLA signaling motifs could play a role in T cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the spleen however, there were significant increases in the frequencies of both CTLA-4 + and TIM-3 + cells in both the CD4 + and CD8 + compartments with combination treatment (Figure 2C). B and T Lymphocyte Attenuator (BTLA) is another inhibitory marker initially expressed on activated T cells, but subsequent downregulation (BTLA − ) is associated with terminal T cell differentiation in the tumor and a decreased capacity to proliferate (34). With combination treatment, BTLA + T cells were significantly decreased in both the CD4 + and CD8 + T cell populations of the spleen (Figure 2D, 2E).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, we noted a significant decrease in the frequency of BTLA + peripheral T cells after concurrent combination treatment. Others have suggested that BTLA − cells are less effective in the tumor, with reduced proliferative capacity and decreased responsiveness to costimulatory molecules (34). We also observed reduced proliferation in concurrent combination-treated T cells in the tumor seven days after the conclusion of treatment (Figure 5A, 5B), despite an increase in proliferation six days prior (Figure 3D).…”
Section: Discussionmentioning
confidence: 99%